An updated VIIRS dark target aerosol product for continuity with MODIS: assessing regional aerosol trends - Sawyer, Virginia; Levy, Robert C.; Mattoo, Shana; Shi, Yingxi R.; Kim, Mijin; Remer, Lorraine A.; Cureton, Geoff (Frontiers in Environmental Science, 2025)
Aerosol optical depth (AOD) is a crucial data record to understand aerosols and their direct and indirect effects on air quality and climate forcing. The Dark Target aerosol retrieval product includes AOD and other properties derived from multispectral satellite imagers, available for MODIS on Terra (from 2000), MODIS on Aqua (from 2002), and VIIRS on Suomi-NPP (from 2012). Although Terra now has over 25 years of observations, the record must continue onto VIIRS beyond the end of the MODIS mission to meet requirements as a Global Climate Observing System (GCOS) climate data record. We present the recent update to version 2.0 of the VIIRS product, which now includes NOAA-20 VIIRS (from 2017) and algorithm improvements. The combined MODIS-VIIRS dataset is examined for consistency and to ascertain aerosol trends. Overall, the VIIRS products show consistency with the MODIS products. To assess regional trends, two time intervals are studied: a 22-year record that compares Terra and Aqua, and a more recent 12-year record (the VIIRS era) that compares three sensors. According to linear regressions of monthly average AOD for each global 1°×1° grid cell, AOD has decreased by between 0.003 and 0.01 per year over parts of China, the United States, Brazil, and much of Europe, while increasing on the same scale over India and parts of Canada, while more modestly but significantly increasing over the southern oceans. For seven regions with significant AOD trends, this study examines the seasonal dependence, relationship to aerosol size parameters, and whether the sign or magnitude of these trends have changed. With high agreement among sensors, we are confident that the Dark Target AOD record can extend into the 2030s and beyond.